Case Report: Combined perioperative extracorporeal membrane oxygenation for acute heart failure caused by mitral regurgitation - Daughtry, Brock; Richardson, John (Frontiers in Cardiovascular Medicine, 2024)
Extracorporeal membrane oxygenation (ECMO) and extracorporeal life support (ECLS) devices are well-established adjunctive treatment measures for patients with heart failure. ECMO can serve as a bridge to transplant in a chronic setting or as a salvage therapy for patients who are unable to be weaned from bypass following cardiac surgery. However, the role of ECMO as a bridge to definitive therapy in a setting of acute heart failure is less established. Similarly, the treatment of patients using combined ECMO and ECLS devices has been, at times, shown to show some benefit; however, these benefits have not been widely studied. In this study, we present the case of a patient who was diagnosed with severe acute onset heart failure secondary to torrential mitral regurgitation following COVID-19 pneumonia. The patient was emergently placed on venoarterial (VA) ECMO with an indwelling centrifugal pump device in the left ventricle. This combination of ECMO and ECLS served as a bridge to open mitral valve replacement 6 days after presentation. Following successful mitral valve replacement, the patient had persistent right ventricular failure, and therefore, a decision was made to incorporate venovenous (VV) ECMO into the VA ECMO circuit. This technique resulted in a VV-VA or VPa-VA configuration, as oxygenated blood was being returned to the pulmonary artery as well as the descending aorta. VA ECMO was discontinued after 4 days of therapy, and the patient was extubated 3 days later. VV ECMO was weaned over the following week, and the patient was decannulated after a total 23 days of ECMO. The patient was then transitioned to inpatient rehabilitation and ultimately discharged home after 18 days. At the 6-month follow-up, the patient was doing well, and objective cardiopulmonary testing revealed normal function. This case is an excellent demonstration of how advanced ECMO and ECLS devices can be used in unique ways through multiple configurations to rescue and optimize patients in the perioperative period.